PENGARUH LATIHAN ABC RUNNING DAN CIRCUIT TRAINNING TERHADAP PENINGKATAN PRESTASI LARI SPRINT 100M PADA ATLET AMTC PANGALENGAN - Jefriagustinus Marulitua Sirumapea (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
Every sprint athlete is required to have excellent anaerobic ability, because anaerobic is one of the most important components in athletics, especially short running numbers such as the 100m-200m-400m number, according to the facts in the field, it was found that their 100m running performance was still low. looks quite low which can be seen from the lack of technique, strength and speed when doing the 100m run, such as when the athlete does the 100m run the leg position is still not lifted and the frequency of the foot is still not fast, the athlete's hand position is also still less attractive or less long. when swinging and the body position is too straight so that during the exercise the athlete cannot get a good time. In the process of solving this research problem, the researcher used a quasi-experimental method with a two-group pretest-posttest design. According to Endang Mulyatiningsih (2013: 96) this two-group pretest-posttest experimental design has 2 data from the measurement results, namely pretest (O1) and posttest (O2). The data analysis technique chosen is of course the two sample t-test. Only one hypothesis was tested, namely there was a difference between the mean pretest and posttest mean values. This two-group pretest-posttest research design compares the two methods of ABC Running and Circuit Training. The sample used in this study was AMTC Pangalengan which was taken randomly as many as 40 samples from 80 samples, after getting the sample the researchers divided into 2 groups, each group consisting of 20 samples, from each group given ABC Running and Circuit Training Tritmen. A did the ABC Running Exercise treatment and for group B did the Circuit Training Exercise, after each group was given the treatment it was found that the ABC Running Exercise method had a very significant effect than the Circuit Trainning Exercise method on Sprint running performance.